Role of the Multidisciplinary Team (MDT) Meetings in Rectal Cancer Management - John, Ajith; Mittal, Rohin (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The management of rectal cancer is complex and requires the expertise of multiple disciplines and various treatment modalities. Multidisciplinary team (MDT) discussions are essential for the optimal management of patients with rectal cancer.An effective MDT is composed of core members from all treating specialities. A specialized radiologist plays a crucial role within the MDT. They are vital to the staging of cancer and the identification of poor prognostic features. Their input is key in planning treatment, including the type and extent of surgery and any neoadjuvant treatment.MDTs must allocate sufficient time for members to prepare for the MDT and adequate time to discuss each case. A final plan of treatment is agreed upon by all attending members and well documented. The patient's care is discussed at multiple points following each treatment modality throughout the cancer treatment journey. Any changes in treatment are rediscussed at the MDT.MDTs have demonstrated the ability to standardize care, leading to improved outcomes. MDTs also improve technical aspects of treatment, such as the quality of surgery and negative margins. These improvements are reflected in improved patient outcomes, including reduced recurrence rates and improved survival.
Keywords: conference; multidisciplinary; rectal cancer; team